The Validity and Legal Force of the Preliminary Sale and Purchase Agreement in the Event of Developer’s Default - Haryadi, Frans; Retnowati, Endang; Fani Martiawan Kumara Putra (Fakultas Hukum Universitas Widya Mataram, 2026)
The Preliminary Sale and Purchase Agreement (in Indonesia known as PPJB) serves as a preliminary contract between developers and consumers prior to the execution of the Deed of Sale and Purchase before a Land Deed Official. The PPJB provides legal certainty for both parties in property transactions during the construction phase. However, in practice, various legal issues arise when developers default, such as delays in property handover, discrepancies in building specifications, or unfinished projects. These situations cause losses to consumers and raise questions regarding the validity and binding legal force of PPJB when developers fail to fulfill their contractual obligations. This study employs a normative legal research method using both statutory and conceptual approaches. The primary legal materials include the Indonesian Civil Code, Law No. 8 of 1999 on Consumer Protection, and relevant regulations in the housing and property sector. The analysis was conducted qualitatively through examination of legal doctrines, principles of contract law, and the application of breach of contract (wanprestasi) within the legal relationship between developers and consumers. The results show that the PPJB remains legally valid as long as it fulfills the requirements for a valid contract under Article 1320 of the Civil Code and is based on the principles of freedom of contract and good faith. However, if the developer commits a default, the PPJB serves as a legal basis for consumers to demand performance, contract termination, or compensation pursuant to Articles 1266 and 1267 of the Civil Code. Therefore, the PPJB retains its binding legal force, but its implementation must be grounded in the principles of justice, legal certainty, and consumer protection in property sale and purchase transactions.